Therapeutic Plasma Exchange in Children With Thrombocytopenia-Associated Multiple Organ Failure: The Thrombocytopenia-Associated Multiple Organ Failure Network Prospective Experience. Issue 3 (March 2019) - Fortenberry, James D.; Nguyen, Trung; Grunwell, Jocelyn R.; Aneja, Rajesh K.; Wheeler, Derek; Hall, Mark; Fleming, Geoffrey; Tarrago, Rod; Buttram, Sandra; Dalton, Heidi; Han, Yong; Easley, Kirk A.; et al.
Abstract : Objective: The objective was to compare the resolution of organ dysfunction, 28-day mortality, and biochemical markers in children with thrombocytopenia-associated multiple organ failure who received therapeutic plasma exchange versus no therapeutic plasma exchange. Design: Observational longitudinal cohort study. Setting: Nine U.S. PICUs. Patients: Eighty-one children with sepsis-induced thrombocytopenia-associated multiple organ failure. Interventions: Therapeutic plasma exchange. Measurements and Main Results: Adjusted relative risk for 28-day mortality was modeled using standard multivariate regression with propensity score weighting to reduce covariate confounding. Change from baseline Pediatric Logistic Organ Dysfunction scores between therapeutic plasma exchange and no therapeutic plasma exchange differed in temporal pattern during the first week ( p = 0.009). By day 4, mean Pediatric Logistic Organ Dysfunction score declined by 7.9 points (95% CI, –10.8 to –5.1) in the therapeutic plasma exchange–treated group compared with no change with no therapeutic plasma exchange. Use of therapeutic plasma exchange was associated with reduced 28-day mortality by multivariate analysis (adjusted relative risk, 0.45; 95% CI, 0.23–0.90; p = 0.02) and by propensity score weighting (adjusted relative risk, 0.46; 95% CI, 0.22–0.97; p = 0.04). Conclusions: Therapeutic plasma exchange use in thrombocytopenia-associated multiple organ failure was associated with a decrease in organ dysfunction. After accounting for several risk factors, 28-day all-cause mortality was lower in children treated with therapeutic plasma exchange compared with those receiving no therapeutic plasma exchange. A multicenter randomized clinical trial is necessary to determine a causal relationship. Abstract : Supplemental Digital Content is available in the text.